The high prevalence of intestinal parasitic infections is associated with stunting among children aged 6-59 months in Boricha Woreda, Southern Ethiopia: a cross-sectional study - Amanuel Yoseph; Hunachew Beyene (BMC, 2020)
Abstract Background Prior studies reported controversial results about the association between intestinal parasitic infections and childhood under-nutrition. We investigated the association of intestinal parasitic infections with under-nutrition among children aged 6-59 months in Boricha Woreda, Southern Ethiopia. Methods This community-based prospective cross-sectional study was carried out from January 1-30, 2019 among 622 children aged 6-59 months. A two-stage stratified sampling procedure was used. Data were collected using a structured, face-to-face interviewer-administered questionnaire and standard anthropometric measurements. The stool specimens were collected using standard technique and examined for the existence and species of intestinal parasites using direct wet mount, Kato Katz and staining technique. We have entered data using Epi Data 3.1 and WHO Anthro software and all analyses were conducted using SPSS version 20. The descriptive analyses were done to find descriptive measures for the socio-demographic and other important variables. Multivariable logistic regression analysis was used to identify factors associated with under-nutrition. Adjusted odds ratios (AORs) with a 95% confidence interval (CI) were computed to assess the presence and strength of associations. Results The total prevalence of intestinal parasitic infection was 48.7% (95% CI, 44.77-52.62). Approximately one-fourth (22%) of the children were infected with moderate intensity infections. Prevalence of stunting, underweight, wasting were 39.3, 24 and 11.6%, respectively. The prevalence of stunting among children infected with the intestinal parasite (59.4%) was significantly higher than the prevalence in non-infected children (20.6%) (p < 0.001). The absence of sanitation facility, living in medium and large family size, lack of shoes wearing practice, consuming raw vegetables and fruits were positively associated with intestinal parasitic infections. The presence of intestinal parasitic infections was positively associated with stunting (AOR = 2.18, 95% CI: 1.36-3.50) but not with wasting (AOR = 0.58, 95% CI: 0.3-1.13) and underweight (AOR: 0.92, 95% CI = 0.55-1.54). Conclusions Under-nutrition and intestinal parasitic infections were serious public health concerns. Consolidating the prevailing water, sanitation and hygiene packages and routine deworming of children aged 6-59 months may aid to decrease the burden of both stunting and intestinal parasitic infection in children. Also, improving modern contraceptive methods utilization to reduce family size is recommended.